Different dietary protein sources influence growth performance, antioxidant capacity, immunity, fecal microbiota and metabolites in weaned piglets - Lianhua Zhang; Xiangshu Piao (Animal Nutrition, 2022)
The inclusion of high-quality proteins are commonly used in swine production. Our research investigated the effects of hydrolyzed wheat protein (HWP), fermented soybean meal (FSBM), and enzyme-treated soybean meal (ESBM) on growth performance, antioxidant capacity, immunity, fecal microbiota and metabolites of weaned piglets. A total of 144 piglets (weaned at 28 d) were allotted to 3 dietary treatments with 6 replicate pens per treatment and 8 piglets per pen. This study included 2 periods: d 0 to14 for phase 1 and d 15 to 28 for phase 2. Dietary treatments contained 15.90% HWP, 15.80% FSBM, and 15.10% ESBM in phase 1, and 7.90% HWP, 7.80% FSBM, and 7.50% ESBM in phase 2, respectively. The ADG of piglets in ESBM was increased (P < 0.05) compared with HWP and FSBM during d 1–28. Compared with HWP and FSBM, ESBM increased (P < 0.05) the ferric reducing ability of plasma (FRAP), and the serum level of superoxide dismutase (SOD) in piglets on d 14, as well as increased (P < 0.05) the serum FRAP level in piglets on d 28. ESBM decreased (P < 0.05) serum levels of DAO and IL-1β in piglets compared with HWP on d 28. ESBM enhanced (P < 0.05) the relative abundance of Bacteroidetes, Oscillospiraceae and Christensenellaceae, as well as reduced the relative abundance of Clostridiaceae in the feces compared with HWP and FSBM. The PICRUSt analysis revealed that the number of gene tags related to degradation of valine, leucine and isoleucine, as well as lysine degradation in ESBM were lower (P < 0.05) than that in HWP and FSBM. ESBM increased (P < 0.05) the fecal butyrate level in piglets compared with FSBM, and ESBM tended to decrease (P = 0.076) the fecal cadaverine level. Overall, ESBM had advantages over HWP and FSBM in improving antioxidant status, immune function, fecal bacteria and metabolites for weaned piglets.